Dedifferentiated Carcinoma of the Endometrium Associated With Low-grade Müllerian Adenosarcoma: A Clinicopathologic Case Report Including the Immunohistochemical and Molecular Profile. (March 2020) - Bai, Shi; Hutchinson, Lloyd M.; Meng, Xiuling; Bai, Hongwei; Cosar, Ediz F.; Khan, Ashraf; Cornejo, Kristine
Abstract : Dedifferentiated carcinoma is defined as undifferentiated carcinoma coexisting with a second component of FIGO grade 1 or 2 endometrioid carcinoma. It is a rare entity with highly aggressive behavior. Dedifferentiated carcinoma combined with another primary uterine tumor is even rarer. We describe a case containing 3 different morphologies comprised of a dedifferentiated carcinoma associated with a low-grade endometrioid carcinoma coexisting with a low-grade Müllerian adenosarcoma. We also used targeted genomic analysis to show all 3 components arise from the same founding clone and identify novel mutations that drive tumor progression. Abstract : Supplemental Digital Content is available in the text.